2010
DOI: 10.1055/s-0029-1243602
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hormone Receptors in Primary Aldosteronism

Abstract: The mechanisms involved in the renin-independent regulation of aldosterone secretion in primary aldosteronism are poorly understood. In ACTH-independent Cushing's syndrome, cortisol secretion can be regulated by the aberrant expression of G-protein coupled receptors (GPCRs) in unilateral tumors and bilateral macronodular adrenal hyperplasia. By analogy, some recent studies identified overexpression or function of several GPCR as a potential cause for excess aldosterone production in some aldosteronomas and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In almost all cases, this has appeared to involve increased expression of receptors normally found in the adrenal (eutopic receptors) rather than expression of receptors not normally expressed in the adrenal (ectopic receptors) (320). Examples of the former (some of which have been discussed earlier in this section) include receptors for ACTH (24), serotonin (277), somatostatin (312), vasopressin (395), glucose-dependent insulinotropic peptide (GIP) (274), gonadotropin releasing and luteinizing hormones (320), and thyroid stimulating hormone (596).…”
Section: Aberrant Adrenocortical G Protein-coupled Receptor Expressiomentioning
confidence: 99%
“…In almost all cases, this has appeared to involve increased expression of receptors normally found in the adrenal (eutopic receptors) rather than expression of receptors not normally expressed in the adrenal (ectopic receptors) (320). Examples of the former (some of which have been discussed earlier in this section) include receptors for ACTH (24), serotonin (277), somatostatin (312), vasopressin (395), glucose-dependent insulinotropic peptide (GIP) (274), gonadotropin releasing and luteinizing hormones (320), and thyroid stimulating hormone (596).…”
Section: Aberrant Adrenocortical G Protein-coupled Receptor Expressiomentioning
confidence: 99%
“…APAs can be distinguished by their size, cell types, hormone oversecretion, and responsiveness to angiotensin 2. In addition, in vitro molecular and immunohistochemistry studies as well as clinical studies with infusion of various compounds in vivo showed that in patients with APA, aldosterone secretion may be regulated also by multiple other factors, mainly arginine, vasopressin, and serotonin (64). However, they can also be differentiated by the extent of hormone suppression by dexamethasone and by the secretion of hybrid steroids, as 18-hydroxy-cortisol (18-OH-F) (65)(66)(67).…”
Section: Clinical Presentation Of Cases With A/cpamentioning
confidence: 99%
“…Therefore, blood aldosterone concentrations that are elevated in relation to a low renin level, which is refl ected by an increase in the aldosterone-to-renin ratio (ARR), do not necessarily prove autonomous aldosterone secretion, being the reason for primary aldosteronism (PA) [ 4 ] . In addition, overexpression of G-protein-coupled membrane receptors is observed in a high proportion of cases with PA and may lead to oversensitivities of aldosteroneproducing adenomas (APAs) to stimuli with an otherwise physiological concentration in the blood [ 5 ] . To circumvent the uncertainties associated with ARR determinations, there is now consensus that the diagnosis of PA be built on the results of confi rmatory testing [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%